Análise sistêmica de impactos de anéis viários na mobilidade e na estrutura espacial urbana: um estudo de caso na região metropolitana de Goiânia - Souza, Suelen Cristina dos Santos de (2022)
To respond a specific need of the transportation system, the ring roads are intended to improve intra-urban traffic, diverting the flow of people and loads. However, like highways, they act in the spatial structuring of territories, providing accessibility, integrating or segregating them. Without multidisciplinary planning, they may provide a temporary improvement in the flow of motorized traffic, but later tend to spatially transform the territory, causing disperse occupation. When this happens, the highway may be absorbed by the local traffic and become an intra-urban flow street, contrary to its implementation objectives. This causes the need to build new concentric outermost ring roads, in a cycle of road multiplication. This practice has its essence in the analytical/specialist approach, which understands planning in a fragmented way when it operates transportation planning separate from territorial planning and implements highways in isolation from other management departments. The research aims, therefore, to identify and analyze in a systemic approach the existing relations between ring roads, mobility and urban spatial structure, creating a methodological procedure for the construction of this subsystem. It is understood that the elements and relations therein reflect its potential impact trends. It is justified by the need for a change in the planning approach, more systemic and articulated among road rings, mobility and urban spatial structure. General Systems Theory is used as a fundamental tool in the methodology approach, that has an exploratory nature and uses systematic and bibliographic review and cartographic analysis. To apply the method, the Metropolitan Region of Goiânia was chosen, in which a section of the proposed ring road was analyzed. As results, a subsystem was identified whose elements and interactions reflect the impacts sought, diagrammed in a network. Although exemplary, the sample identified reveals crucial points of the planning that must receive attention to fulfill the intended purpose, considering the territorial, environmental, political-social and transportation impacts.